2020
DOI: 10.21203/rs.3.rs-34702/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ARIMA Models for Predicting the End of COVID-19 Pandemic and the Risk of a Second Rebound

Abstract: Globally, many research works are going on to study the infectious nature of COVID-19 and every day we learn something new about it through the flooding of the huge data that are accumulating hourly rather than daily which instantly opens hot research topics for artificial intelligence researchers. However, the public’s concern by now is to find answers for two questions; 1) when this COVID-19 pandemic will be over? and 2) After coming to its end, will COVID-19 return again in what is known as a second rebound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…7.85 billion and the number of people completed vaccination is 3,289,529,390 [51] . To attain the most accurate forecast, the parameters of the SARIMA model are investigated using a grid search approach [46] , [27] . Finally, the best SARIMA model’s parameters are estimated and used to forecast the total number of vaccination for the next 30 days.…”
Section: Experimental Results and Evaluationsmentioning
confidence: 99%
See 1 more Smart Citation
“…7.85 billion and the number of people completed vaccination is 3,289,529,390 [51] . To attain the most accurate forecast, the parameters of the SARIMA model are investigated using a grid search approach [46] , [27] . Finally, the best SARIMA model’s parameters are estimated and used to forecast the total number of vaccination for the next 30 days.…”
Section: Experimental Results and Evaluationsmentioning
confidence: 99%
“…As Novel Corona Pandemic COVID-19 reports a major warning to the international health systems, cooperation is required by all the countries to combat it. Zohair et al [4] , [27] , [28] , [29] , [30] , [31] , [27] proposed different regressor machine learning models for the COVID-19 Pandemic and it even started the second wave in many countries before a year has passed. Moreover, the models are utilized to estimate the effect of climate on the transmission of COVID-19 by extracting connections between the number of asserted cases and the atmosphere factors on explicit areas.…”
Section: Related Workmentioning
confidence: 99%
“…Another study conducted for forecasting different countries COVID-19 trend demonstrated stable condition for China, stationary trend for South Korea while Thailand showed controlled condition 18 . Based on a study, for predicting the end of COVID-19 by using this model expected that top countries COVID-19 infection will slow down by October, 2020 39 . In contrast, in Saudi Arabia and Nigeria this model forecasts highly increased of daily case with cumulative daily cases within one month 4041 .…”
Section: Discussionmentioning
confidence: 99%
“…As Novel Corona Pandemic COVID-19 reports a major warning to the international population health, collaboration is needed by all the nations to combat it [ 24 ]. The media and other web-based media channels should morally introduce the pertinent and right reports to expand inspiration among the overall population as opposed to introducing one-sided data; such coverage may only serve to further divide people and cause fear [ 16 , 31 ].…”
Section: Related Workmentioning
confidence: 99%